수지의 종적 Bracket 골단에 대한 수술적 치료 - 김성수(Sung Soo Kim); 김기웅(Ki Woong Kim); 김정호(Jung Ho Kim); 이찬수(Chan Soo Lee) (The journal of the Korean Orthopaedic Association, 2020)
목적: 종적 bracket 골단으로 인한 측만지 변형에서 교정절골술, 골단판 유리술의 수술적 치료를 시행한 환자에서 임상적 및 방사선적 결과를 평가하고자 하였다. 대상 및 방법: 1999년 3월부터 2017년 4월까지 측만지를 주소로 내원하여 종적 bracket 골단을 확인하고 교정절골술 및 골단판유리술의 수술을 시행한 환아 11명(27예)을 대상으로 의무기록 및 방사선 사진을 통해 수술 전후의 근위 및 원위 지간 관절의 관절 운동 범위와 환자의 외관적, 기능적 만족도, 이환된 수지의 편위된 정도를 평가하여 환자군을 교정절골술을 시행한 군과 골단판 유리술을 시행한 군으로 나누어 임상적 및 방사선적 결과를 후향적으로 검토하여 수술 방법에 따른 차이를 비교하였다. 결과: 수술 방법에 따라 교정절골술을 시행한 환자군의 수술을 시행한 평균연령은 10.3세였으며 수술 전 이환된 수지의 편위각은평균 25.7도에서 수술 후 13.5도로 평균 교정률은 47.4%였다. 골단판 유리술을 시행한 환자군의 수술을 시행한 평균 연령은 6.0 세였으며 수술 전 평균 24.5도, 수술 후 10.7도의 평균 편위각을 보였다. 평균 교정률은 59.4%였다. 교정절골술을 시행한 군과 골단판 유리술을 시행한 군 간의 수술 전후 및 교정 각도에 대해 비교한 결과 통계적으로 유의한 차이를 보이지 않았으나 각각의 환자군에서 교정 정도는 통계적으로 유의한 호전 정도를 보였다. 근위 및 원위 지간 관절의 술 후 최종 추시 시 관절 운동 범위는 수술 전 관절 운동 범위와 유의한 차이가 없었다. 기능적, 외관적 만족도에서도 만족하는 경향을 보였다. 결론: 종적 bracket 골단으로 인한 측만지 변형을 보이는 환자에서 절대연령 및 골연령, 방사선적 진행 단계에 따라 교정절골술이나 골단판 유리술을 선택적으로 시행할 수 있으며 두 수술 방법 모두 양호한 임상적 결과와 변형 교정을 보였다. Purpose: To describe the clinical and radiology results of a surgical treatment for clinodactyly due to a longitudinal epiphyseal bracket. Materials and Methods: This study analyzed the records of 11 patients (27 case) with clinodactyly due to a longitudinal epiphyseal bracket who underwent an osteotomy or physiolysis between March 1999 and April 2017. The preoperative range of motion of the proximal and distal interphalangeal joints, the subjective satisfaction of the patient, and the degree of angulation to the ulnar side were examined. The patients were classified into two groups: osteotomy and physiolysis. The results were reviewed retrospectively and compared according to the surgical method. Results: The mean age of the patients who underwent osteotomy was 10.3 years. The average preoperative angle was 25.7° and the average postoperative angle was 13.5° the mean correction rate was 47.4%. The mean age of the patients who underwent physiolysis was 6.0 years the mean preoperative angle was 24.5° and the postoperative angle was 10.7°. The average correction rate was 59.4%. No significant difference in the correction angles was observed between the group who underwent the correction osteotomy and the group who underwent the osteotomy. In each group, the postoperative correction was statistically significant. The range of motion at the last follow-up was not significantly different from the preoperative range of motion. Conclusion: In patients with clinodactyly due to longitudinal epiphyseal bracket, osteotomy or physiolysis may be performed selectively according to age, bone age, and radiological progression. Both surgical methods showed good clinical results and deformity correction. KCI Citation Count: 0